Linkage analysis in adenomatous polyposis coli: the use of four closely linked DNA probes in 20 UK families. Issue 10 (October 1991) - Cachon-Gonzalez, M B; Delhanty, J D; Burn, J; Tsioupra, K; Davis, M B; Attwood, J; Chapman, P
Abstract : Linkage analysis was carried out on 20 unselected UK families segregating for adenomatous polyposis coli (APC) using four closely linked DNA probes. Significant lod scores were obtained between APC and three markers: pi 227 (D5S37) theta = 0.16; C11p11 (D5S71) theta = 0.10; and YN5.48 (D5S81) theta = 0.00. The fourth, ECB27 (D5S98), gave low lod scores. The APC gene showed linkage with at least one of the probes used in all families, which is in agreement with previous publications. Combined lod scores are now sufficiently high to allow the use of these probes in presymptomatic diagnosis. Despite the fact that 61% of persons at risk were informative for at least one DNA marker, only 15% were informative with flanking probes. One prenatal diagnosis was performed where the initial request had been for sterilisation.